The Role of Stakeholders in the Collaborative Development of Bawean Island Tourism - I Gede Eko Putra Sri Sentanu; Aulia Puspaning Galih; Rinaldo Albertus Triprasetyo (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Tourism development on the island of Bawean requires collaboration from all parties who have interests (stakeholders). Stakeholders consist of the government, the community, the private sector, academia and the mass media. This collaboration is very important because each stakeholder actor has different capabilities and limitations. The government has a role as a regulator, the private sector and the community as implementers, while academics and the media are supporting actors. The research aims to find out how the collaboration carried out by these stakeholders includes the important role of each stakeholder actor. And what kind of collaboration is done between these actors. In addition, it is also explored more deeply about the conditions of tourism development on the island of Bawean in order to know the steps that can be suggested and the collaboration model built and implemented by a group of stakeholders. It is hoped that this research will be able to produce concepts that can be offered to stakeholders, especially the government so that they can actually be implemented. This research is a qualitative research with a case study approach. The focus in this research is first, the role of stakeholders which includes identification of stakeholders and categorization of stakeholders. Second, stakeholder collaboration which includes the relationship between stakeholders and forms of stakeholder collaboration. The research location is located on Bawean Island with the research sites being the Gresik Regency Tourism and Culture Office and the Bawean Island UPT. Data collection techniques are interviews, observation and documentation. The results of this research are expected to reveal a lot and identify stakeholders and collaboration models that can be implemented and developed.